Adjuvant FOLFOX+Nab-Paclitaxel (FOLFOX-A) for Pancreatic Cancer: A Brown University Oncology Research Group Phase II Study (BrUOG295). (December 2020) - Raufi, Alexander G.; Breakstone, Rimini; Leonard, Kara; Charpentier, Kevin; Beard, Rachel; Renaud, Jennifer; Cavanaugh, Lindsey; Sturtevant, Ashlee; MacKinnon, Kelsey; Almhanna, Khaldoun; Olszewski, Adam; Safran, Howard P.
Abstract : Objectives: Multiple clinical trials have established a role for adjuvant chemotherapy for patients with pancreatic ductal adenocarcinoma. Adjuvant FOLFIRINOX increases survival as compared with gemcitabine but with increased toxicity. FOLFOX+nab-paclitaxel (FOLFOX-A) was developed by the Brown University Oncology Research Group (BrUOG) as an alternative to FOLFIRINOX. This phase II trial explored the feasibility and toxicity of adjuvant FOLFOX-A in patients who have completed resection for pancreatic ductal adenocarcinoma. Patients and Methods: Patients with resected pancreatic ductal adenocarcinoma were eligible. The primary objective was to determine the feasibility of adjuvant FOLFOX-A. Patients experiencing grade 2 neuropathy received a 20% reduction of oxaliplatin. Secondary end points were disease-free survival, and overall survival. Results: Between June 2014 and October 2018, 25 patients were enrolled following surgical resection. The median number of cycles completed was 9.5. Median disease-free survival was 19.7 months (95% confidence interval, 10.3 to not reached) and median overall survival was 53.5 months (95% confidence interval, 24.2 to not reached). The most common treatment-related grade 3 or greater adverse events were fatigue (58%), nausea (13%), and neutropenia (26%). Fourteen patients had grade 2 neuropathy (58%) and 1 patient (4%) had grade 3 neuropathy. Only 2 patients (8%) had grade 3 diarrhea. Conclusions: Adjuvant FOLFOX-A is a feasible multi-agent adjuvant treatment regimen and, with further validation, could be an alternative to FOLFIRINOX.